Near-field coupling of a levitated nanoparticle to a photonic crystal cavity - Magrini, Lorenzo; Norte, Richard A; Riedinger, Ralf; Marinković, Igor; Grass, David; Delić, Uroš; Gröblacher, Simon; Hong, Sungkun; Aspelmeyer, Markus (arXiv.org, 2019)
Quantum control of levitated dielectric particles is an emerging subject in quantum optomechanics. A major challenge is to efficiently measure and manipulate the particle's motion at the Heisenberg uncertainty limit. Here we present a nanophotonic interface suited to address this problem. By optically trapping a 150 nm silica particle and placing it in the near field of a photonic crystal cavity, we achieve tunable single-photon optomechanical coupling of up to \(g_0/2π=9\) kHz, three orders of magnitude larger than previously reported for levitated cavity optomechanical systems. Efficient collection and guiding of light through the nanophotonic structure results in a per-photon displacement sensitivity that is increased by two orders of magnitude compared to conventional far-field detection. The demonstrated performance shows a promising route for room temperature quantum optomechanics.